A survey of limit laws for bootstrapped sums - Sándor Csörgő; Andrew Rosalsky (International Journal of Mathematics and Mathematical Sciences)
Concentrating mainly on independent and identically distributed (i.i.d.) real-valued parent sequences, we give an overview of first-order limit theorems available for bootstrapped sample sums for Efron's bootstrap. As a light unifying theme, we expose by elementary means the relationship between corresponding conditional and unconditional bootstrap limit laws. Some open problems are also posed.